2016
DOI: 10.1007/s10649-016-9698-3
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between graphical arguments and verbal-symbolic proofs in a real analysis context

Abstract: We examine a commonly suggested proof construction strategy from the mathematics education literature-that students first produce a graphical argument and then work to construct a verbal-symbolic proof based on that graphical argument. The work of students who produce such graphical arguments when solving proof construction tasks was analyzed to distill three activities that contribute to students' successful translation of graphical arguments into verbal-symbolic proofs. These activities are called elaboratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…To overcome such difficulties, two types of actions can be taken. The first type is "rewarranting" (Zazkis et al, 2016). Rewarranting, as employed by Zazkis et al, is related to translation from graphical warrants to verbal-symbolic warrants; in our study, instead, it involves adding additional reasons in order to make sufficient warrants, as illustrated in Moe's case in Section 5.2.3.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To overcome such difficulties, two types of actions can be taken. The first type is "rewarranting" (Zazkis et al, 2016). Rewarranting, as employed by Zazkis et al, is related to translation from graphical warrants to verbal-symbolic warrants; in our study, instead, it involves adding additional reasons in order to make sufficient warrants, as illustrated in Moe's case in Section 5.2.3.…”
Section: Discussionmentioning
confidence: 92%
“…Following Pedemonte (2007) and Zazkis et al (2016), we used the simplified version of Toulmin's (2003) framework to analyze students' attempts at proof validation and modification. This simplified framework consists of the claim (C) being argued, the data (D) used to demonstrate the claim, and the warrant (W) describing how the data support the claim.…”
Section: Framework and Data Analysismentioning
confidence: 99%
“…The construction of arguments that meet the standard of proof is often the last step in a complex and multifaceted activity typically referred to as proving that includes also other processes such as the following: work with examples or exploration of particular cases, identification of patterns and generation or refinement of conjectures or other Students' proof constructions in mathematics 157 kind of mathematical claims, and attempts to develop informal arguments for these mathematical claims that may offer insight, or ultimately translate, into a proof (e.g. Mason, 1982;Boero et al, 1996;Weber & Alcock, 2004;Mariotti, 2006;Stylianides, 2007Stylianides, , 2008Alcock & Inglis, 2008;Zazkis et al, 2008Zazkis et al, , 2016. In this article, I focus on the presentation of mathematical arguments whose constructors perceive they meet the standard of proof and who might have engaged previously in some other processes within the broader activity of proving.…”
Section: Introductionmentioning
confidence: 99%
“…Research falling into the first category has highlighted the important role that semantic reasoning can play in proof generation. Various types of semantic reasoning have been shown to inform proof generation (Gibson 1998;Sandefur et al 2013;Zazkis et al 2016). For example, drawing diagrams (Gibson 1998), generating examples (Sandefur et al 2013), conjecture generation (Boero 1999;Pedemonte 2007), and even the generation of fully formed semantic arguments (Zazkis et al 2016), have all been shown to inform students' proof generation.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of semantic reasoning have been shown to inform proof generation (Gibson 1998;Sandefur et al 2013;Zazkis et al 2016). For example, drawing diagrams (Gibson 1998), generating examples (Sandefur et al 2013), conjecture generation (Boero 1999;Pedemonte 2007), and even the generation of fully formed semantic arguments (Zazkis et al 2016), have all been shown to inform students' proof generation. Additionally, some researchers have argued that the generation of certain types of proofs is difficult without conceptual insights gained from semantic reasoning (Raman 2003;Weber and Alcock 2004).…”
Section: Introductionmentioning
confidence: 99%